KONTRIBUSI PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH SEBELUM DAN SELAMA MASA PANDEMI COVID-19 KABUPATEN TABALONG TAHUN 2017-2022 - Tria Erika Damayanti; Rahmawati, Rini; Wardhana, Ali (Universitas Lambung Mangkurat, 2022)
Restaurant tax is one source of revenue that contributes to increasing PAD. This research aims to determine the contribution of restaurant taxes to Original Regional Income before and during the Covid-19 pandemic in Tabalong Regency 2017-2022. The type of data used is quantitative, while the data source is secondary. Data collection techniques using interviews and documentation. The data analysis technique is descriptive analysis. The results of this research show that the contribution of restaurant taxes to PAD in Tabalong Regency 2017-2022 is still very low, seen from the average contribution of restaurant taxes before and during the Covid-19 pandemic, the percentage of which decreased by 1.51%.